EDUCATIONAL OPERATION AND GUIDELINES FOR THE DEVELOPMENT OF STUDENT SUPPORT SYSTEM IN EXTRA-LARGE SCHOOL FROM UNDER THE SURIN PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Pradabsuk, Phanuvit; Thiangphak, Dr. Pimprith (Journal of Interdisciplinary Development (Humanities and Social Sciences), 2026)
The objectives were 1) to study the operation of the student support system of Special Large Schools and 2) to propose guidelines for developing the operation of the Student Support System in extra-large schools. This research is quantitative and qualitative research. The samples used in the quantitative research were 15 administrators and 241 teachers in a large special school. The researchers determined the sample size by opening the ready-made tables of Krejcies & Morgan and sampling. with a simple random method to find the proportions of each school and answer open-ended questions of 30 people. It was a 5-level estimation scale questionnaire with a confidence value of 0.90. The statistics used in the data analysis were frequency distribution, percentage, mean, standard deviation, and content analysis. The results of the research showed that 1) operation of the student support system in extra-large schools. Overall, the performance was at a high level ( = 4.05). Considering individual aspects, it was found that the aspect with the highest average was student promotion and development ( = 4.54), followed by knowing students individually ( =4.39), referring students ( = 4.10), screening students ( =4.05), while the aspect with the lowest mean was prevention and problem solving ( =4. 00) and 2) guidelines for the development of student support systems in extra-large schools, that educational institutions should have plans to promote and develop activities that were consistent with students’ behaviors. To encourage students to develop themselves to their full potential. Developing a tool for collecting student health data, and promoting data collection on family and student living conditions. Promoting the analysis of individual student data. Developing a systematic plan for the preparation of student referral information Administrators should pay more attention to the operation of the student support system in preventive and problem-solving operations. Teachers should promote prevention and solution to current problems. Giving equal attention to all students. Keeping close attention to students and finding ways to help, both preventing and solving student problems from becoming a social problem. Moreover, this research, it would be useful to the administrators of other educational institutions. Using as the guidelines to improve and develop the operation of the student support system of their own schools to be better consistent and appropriate to the context.